Drivers of Variability in 90-day Cost for Primary Single-level Microdiscectomy. Issue 6 (30th May 2018) - Chotai, Silky; Sivaganesan, Ahilan; Parker, Scott L; Sielatycki, John A; Archer, Kristin R; Nian, Hui; Stephens, Eric; Aaronson, Oran S; McGirt, Matthew J; Devin, Clinton J
Abstract: BACKGROUND: The healthcare reimbursement models are rapidly transitioning to pay-per-performance episode of care payment models. These models, if designed well, must account for the variability in the cost of index surgeries during the global period. OBJECTIVE: To analyze the variability in 90-d cost and determine the drivers of the variability in total 90-d cost associated with single-level microdiscectomy. METHODS: A total of 203 patients undergoing primary microdiscectomy for degenerative lumbar conditions were included in the study. The total 90-d cost was derived as the sum of cost of surgery, cost associated with postdischarge utilization. A multivariable linear regression model for total 90-d cost was built. RESULTS: The mean total cost within 90-d after single-level primary microdiscectomy was 7962 ± 2092. In a multivariable linear regression model, obesity, history of myocardial infarction, factors that lengthen the time of surgery and hospital stay, complications and readmission within 90-d, postdischarge healthcare utilization including emergency room visits, time to opioid independence, number of days on nonopioid pain medications, diagnostic imaging, and the number of days in outpatient and inpatient rehabilitation contribute to the total 90-d cost. The model performance as measured by R 2 is 0.76. CONCLUSION: Utilizing prospectively collected data, we highlight major drivers of variation in cost following a single-level primary microdiscectomy. Our model explains about three-quarters of the variation in cost. The risk-adjusted cost estimates powered by models such as the one presented here can be used to formulate a sustainable total 90-d episode of care bundle payment.